Blockchain Technology for Renewable Energy Transactions and Grid Management - Mousa, Sura Hamed; Hussain, Refat Taleb; Hassan, Zahraa Mohammed; Qasim, Nameer Hashim; Mahdi, Akram Fadhel; Batumalay, M. (Malikussaleh University, Aceh, Indonesia, 2025)
The transition to renewable energy sources necessitates novel solutions for decentralized energy management, secure transactions, and transparent regulatory compliance. This paper presents the design and evaluation of a blockchain-based system addressing these challenges through peer-to-peer (P2P) energy trading, dynamic smart grid coordination, and automated Renewable Energy Certificate (REC) lifecycle management. Employing a hybrid methodology that combined qualitative stakeholder interviews with a six-month quantitative simulation of 50 prosumers, our Ethereum Proof-of-Stake (PoS) platform was assessed for efficiency, latency, and stability. The results indicate superior performance over traditional models, revealing significant gains in energy transfer efficiency, marked reductions in transaction latency under various network loads, near-elimination of REC fraud, and enhanced grid frequency stability. This study empirically confirms that decentralized architectures can augment or replace centralized utility models, establishing blockchain as a viable infrastructure for future smart grids and informing policy decisions needed to create a more resilient and equitable energy market for energy efficiency.